Health surveillance indicators for diet and physical activity: what is available in European data sets for policy evaluation? - Stanley, Isobel; Neumann-Podczaska, Agnieszka; Wieczorowska-Tobis, Katarzyna; Mensink, Gert B. M.; Rosas, Lina Garnica; Do, Stefanie; Abu-Omar, Karim; Woods, Catherine; Ahrens, Wolfgang; Hebestreit, Antje; Murrin, Celine (European Journal of Public Health, 2022)
Background Policies targeting diet and physical activity have the potential to improve health and well-being at a population level. However, the impact of these policies in Europe is currently unknown. Based on existing data, as well as on a needs assessment, we derived a catalogue of indicators that can be employed to evaluate such policies. These indicators may also inform the further development and harmonization of surveillance systems. Methods Forty EU experts agreed on a list of key indicators and ranked their priority for future surveillance. We mapped these indicators onto variables provided by ongoing European surveillance systems. Using a Likert scale (well matched, somewhat matched, poorly matched, unmatched), we assessed the suitability of these variables as measures for the indicators. Results Key indicators included behaviour outcome indicators relating to diet (n = 72) and physical activity and sedentary behaviour (n = 67) as well as upstream determinants of these behaviours. It was possible to map 72% of diet indicators and 86% of physical activity and sedentary behaviour indicators onto at least one variable in an ongoing surveillance system. Conclusions Current monitoring and surveillance systems focus mainly on measuring 'downstream' indicators, while gaps exist in policy and environmental level data in dimensions such as inequality, funding and resources and governance.
CRIS-Team WoS Importer:2022-06-03